Polysaccharide Hydrogel-Assisted Biosensing Platforms for Point-of-Care Use - Sang-Uk Kim; Young Jun Kim; Tae Hee Lee (Biosensors)
Point-of-care (POC) use is one of the essential goals of biosensing platforms. Because the increasing demand for testing cannot be met by a centralized laboratory-based strategy, rapid and frequent testing at the right time and place will be key to increasing health and safety. To date, however, there are still difficulties in developing a simple and affordable, as well as sensitive and effective, platform that enables POC use. In terms of materials, hydrogels, a unique family of water-absorbing biocompatible polymers, have emerged as promising components for the development of biosensors. Combinations of hydrogels have various additional applications, such as in hydrophilic coatings, nanoscale filtration, stimuli-responsive materials, signal enhancement, and biodegradation. In this review, we highlight the recent efforts to develop hydrogel-assisted biosensing platforms for POC use, especially focusing on polysaccharide hydrogels like agarose, alginate, chitosan, and so on. We first discuss the pros and cons of polysaccharide hydrogels in practical applications and then introduce case studies that test different formats, such as paper-based analytical devices (PADs), microfluidic devices, and independent platforms. We believe the analysis in the present review provides essential information for the development of biosensing platforms for POC use in resource-limited settings.